FAKTOR - FAKTOR YANG MEMPENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) (Studi Pada Perusahaan Real Estate Dan Property Yang Terdaftar Di Bursa Efek Indonesia) - Milawati, 12.05.52.0141; Indarti, MG Kentris (Students Journal of Accounting and Banking, 2016)
This study was conducted to examine and analyze the influence of the persistence of earnings, growth, systematic risk, capital structure (leverage) and the size of the company (size) to Earnings Response Coefficient (ERC). Sampling based on purposive sampling method of real estate and property companies listed on the Indonesian Stock Exchange in the period 2011-2014. Based on the criteria then obtained a sample of 119 companies. The statistical method used is multiple regression models with SPSS.Â The results showed earnings persistence significant positive effect on the ERC, the companys growth significantly negative influence to the ERC, while the systematic risk, capital structure (leverage), firm size (size) does not significantly influence the ERC. Adjusted R Square value of 0.27 which can be concluded that only 27% Earnings Response Coefficient (ERC) significantly explained by the persistence of earnings, growth, systematic risk, capital structure (leverage) and firm size (size), while 73% are explained by other variables outside the research model.Keywords: Earnings Response Coefficient (ERC), The Persistence Of Earnings, Growth, Systematic Risk, Capital Structure (Leverage), Firm Size (Size)